Sustainable Aquaculture Techniques - Patricia Hernandez- Vergara, Martha; Ivan Perez-Rostro, Carlos (IntechOpen, 2014)
This book presents some innovative developments in sustainable aquaculture practices in the context of environmental protection and seafood production techniques. The chapters are written by experts in their respective areas, so that their contribution represents the progress of their research, which is intended to mark the current frontier in aquaculture practices. Every chapter presents techniques that contribute to good aquaculture practices, where direct and vital nutrition and food, as a source of energy and biomass generation, is fundamentally based. We hope this book supports producers and researchers in their activities and helps to maintain a spirit of environmental protection in the context of production of high quality, nutritional food.